Biomechanical characteristics of elite female australian rules football preferred and non-preferred drop punt kicks - Cust, E.; Ball, K.; Sweeting, A.; Robertson, S. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
While Australian Rules kick biomechanics has been researched considerably, there is yet to be focus specifically on women participants. Elite female Australian Rules football drop punt kick characteristics were collected from 15 elite female participants for both the preferred and non-preferred legs. All participants undertook a 20-kick protocol captured by a 3-dimensional motion analysis camera system. Preferred leg kicks produced faster foot velocities prior to foot-ball contact, 18.0 ± 1.2 m.s-1 preferred, 16.2 ± 1.3 m.s-1 non-preferred, and faster ball velocities post foot-ball contact, 24.7 ± 1.4 m.s-1 preferred, 21.6 ± 2.0 m.s-1 non-preferred. Differences in movement patterns of the hip and knee joint segments were shown between kick leg preferences; hip angular velocity 94.4 ± 75.9 °/s preferred and 126.2 ± 66.3 °/s non-preferred, knee angular velocity 1384.8 ± 415.2 °/s preferred and 1013.6 ± 230.2 °/s non-preferred. Research results identified the changes in elite women`s dr op punt kick mechanics in comparison to leg preference, which can be viewed against senior and junior men`s Australian football kick analysis findings. The current research information could be of benefit to practitioners in linking targeted field coaching cues and conditioning programs tailored to identified kick skill and movement deficiencies.